FRGS Grants 2021 - Nabilah Filzah, Mohd Radzuan (Faculty of Computing, 2021)
PEKAN 7 September 2021- Congratulations to the following FK academicians for securing the research grant under Skim Geran Penyelidikan Fundamental (FRGS) Phase 1 of the year 2021